Religious activity of the population as factor of influence on the demographic processes - Kostaschuk, Ivan (Journal of Education, Health and Sport, 2019)
This article studies the peculiarities of influence of religious activity of the population on the course of the demographic process on a certain territory. The territory of Ukraine was selected for research. It is established that the religious activity of the population significantly determines the process of birth and death of the population, due to the number of abortions, suicides, the average number of children in the family, and so on. To establish the relationship and its justification, a method of linear correlation was chosen which helped to establish different degrees of mutual influence. The most noticeable impact on demographic components is presented in the article.